The resale right: approximation to the EU acquis - MAIDANYK, Любов (Ius Modernum, 2023)
Changes to the resale right in Ukrainian copyright in connection with the approximation to EU law determine the relevance of this topic. The purpose of the resale right is to provide the author of the original work of art and his or her heirs with the opportunity to benefit from the economic success of such a work. However, due to changes in the Ukrainian legislation and the development of modern technologies a number of problematic issues appear. The aim of the article is to analyse the latest legislative changes in connection with the approximation to EU law and the practice of applying the resale right in the framework of NFT. The methods applied are: structural-logical and system-functional analysis; abstraction and generalization; analogies and comparison; recommendatory. The legislation of Ukraine on the resale right and the state of implementation of the provisions of the Directive on the resale right have been analysed. The practice of concluding smart contracts on NFTs for the possible application of the resale right is explored. It is proposed to exclude from Ukrainian legislation the original manuscripts of literary and musical works from the list of objects to which the resale right is applied. It is concluded that the obligation to pay remuneration for the resale right arises in relation to any agreement for the purchase and sale of the original work between individuals which will be carried out through public online platforms. The application of the principle of reciprocity with regard to the resale right, provided for in Part 2 of Article 14 of the Berne Convention, precludes the obligation to pay remuneration if the party to the resale of the painting through the online platform is a person whose country of origin legislation does not provide for the resale right. It has been analysed that one of the functions of a smart contract is that the share of resale is automatically paid to the author of the work whenever NFTs are resold. It is concluded that such a provision is of a contractual nature, and therefore, despite the similarity of such a mechanism with the construction of the resale right, the latter cannot be applied to NFTs.